15 Jahre Kunsthalle Wien. - Matt, Gerald (Wien : Kunsthalle Wien, 2007)
Arnold, Martin ; Bareikis, Aidas ; Barney, Matthew ; Bechtold, Gottfried ; Beckett, Samuel ; Beecroft, Vanessa ; Birnbaum, Dara ; Boltanski, Christian ; Bourgeois, Louise ; Brem, Richard ; Broodthaers, Marcel ; Bruguera, Tania ; Cai Guo-Qiang ; Chalmers, Catherine ; Chen Zhen ; Cohen, Steven ; Djurberg, Nathalie ; Faccio, Luca ; Feldmann, Hans-Peter ; Gappmayr, Heinz ; Giacometti, Alberto ; Goldin, Nan ; Graham, Rodney ; Herrmann, Matthias ; Hesse, Eva ; Hill, Gary ; Hoeck, Richard ; Holzer, Jenny ; Horn, Rebecca ; Kim, Soo-Ja ; Knispel, Florian ; Komar & Melamid ; Kozek, Peter ; Kusolwong Surasi ; Lang, Helmut ; Lattanzi, Maria Pia ; Leitner, Paul Albert ; Ligthart, Theo ; Lin, Michael ; Logar, Ernst ; Margolles, Teresa ; Matelli, Tony ; McQueen, Steve ; Miller, John ; Model, Lisette ; Moffatt, Tracey ; Morath, Inge ; Nauman, Bruce ; Neshat, Shirin ; Niedermayr, Walter ; Pelesjan, Artavazd (Artur) A. ; Pettibon, Raymond ; Pope.L, William ; Riello, Antonio ; Rist, Pipilotti ; Rondinone, Ugo ; Sala, Anri ; Schlemmer, Oskar ; Schönberg, Arnold ; Selichar, Günther ; Senoner, Peter ; Shonibare, Yinka ; Sierra, Santiago ; Smithson, Robert ; Steinbrecher, Erik ; Swallow, Ricky ; Teller, Juergen ; Tomic, Milica ; Warhol, Andy ; Wong Hoy Cheong ; X, Robert Adrian ; Yang Fudong ; Yayoi, Kusama
Erschienen anlässlich der 15-Jahresfeier der Kunsthalle Wien, Wien, 7. bis 9.November 2007
boek